2019
DOI: 10.1158/1538-7445.sabcs18-ot2-06-05
|View full text |Cite
|
Sign up to set email alerts
|

Abstract OT2-06-05: A randomized phase II study of peri-operative ipilimumab, nivolumab and cryoablation versus standard peri-operative care in women with residual triple negative early stage/resectable breast cancer after standard-of-care neoadjuvant chemotherapy

Abstract: Background: Triple negative breast cancer (TNBC) is a biologically distinct subtype with high risk of early relapse, particularly for patients who do not achieve a pathological complete response (pCR) after neoadjuvant chemotherapy (NAC), with an event free survival of < 60% at 3 years. Physical disruption of tumors with cryoablation (cryo) induces inflammation and releases antigens that can activate tumor-specific immune responses. In pre-clinical studies, the combination of cryo with checkpoint inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…One of these trials focuses on the number of adverse events as the primary outcome of cryoablation, Nivolumab (anti-PD-L1), and Ipilimumab (anti-CTLA-4) treatment in patients with early-stage breast cancer [42]. Another phase II trial is investigating the impact of pre-operative cryoablation, Nivolumab, and Ipilimumab treatment in patients with triple-negative breast cancer after neoadjuvant chemotherapy [43].…”
Section: Cryosurgery and Immunotherapymentioning
confidence: 99%
“…One of these trials focuses on the number of adverse events as the primary outcome of cryoablation, Nivolumab (anti-PD-L1), and Ipilimumab (anti-CTLA-4) treatment in patients with early-stage breast cancer [42]. Another phase II trial is investigating the impact of pre-operative cryoablation, Nivolumab, and Ipilimumab treatment in patients with triple-negative breast cancer after neoadjuvant chemotherapy [43].…”
Section: Cryosurgery and Immunotherapymentioning
confidence: 99%
“…A pilot study utilizing cryoablation with ipilimumab demonstrated safety in women with operable breast cancer [106]. A phase II randomized study of perioperative ipilimumab, nivolumab, and cryoablation versus standard care in resectable TNBC following standard of care neoadjuvant therapy is ongoing [107]. The number of cryoablative treatments and timing for optimal outcome needs to be established; in one retrospective observational study of patients with metastatic breast cancer, multiple cryoablations were associated with greater median OS compared with single cryoablations (76 months vs 48 months, p = 0.0005) [108].…”
Section: Antigenic Cell Death: Radiation Therapy and Cryoablationmentioning
confidence: 99%